Innovations in sharia tax governance: Aligning sharia principles with the national tax system - Erison, Fadya Anjani Ramadhita; Putri, Denissia Maynda; Amanda, Elly Yulia; A’yun, Qurrota; Laksmi, Ayu Chairina (Proceeding International Conference on Accounting and Finance, 2024)
Tax is an activity carried out by the state on individuals and entities and is coercive in nature. The income from tax collection is given to the state for state needs and the prosperity of the people. This tax has certain characteristics according to Sharia in Islam. Tax collection is carried out through various systems in accordance with the provisions determined by the state. Apart from that, tax collection must also be in accordance with the basic provisions that apply in Indonesia. In Indonesia itself there are several basic provisions for tax collection that apply. There are two positions of tax in Islam, one of which is the view of approving the existence of taxes, apart from that, in Islam, taxes have Islamic governance, compliance with sharia principles, making it a thing that differentiates them in general.